2013
DOI: 10.3390/s130809669
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Sensor Interrogation Using Wavelength-Swept Laser with a Polygon-Scanner-Based Wavelength Filter

Abstract: We report a high-speed (∼2 kHz) dynamic multiplexed fiber Bragg grating (FBG) sensor interrogation using a wavelength-swept laser (WSL) with a polygon-scanner-based wavelength filter. The scanning frequency of the WSL is 18 kHz, and the 10 dB scanning bandwidth is more than 90 nm around a center wavelength of 1,540 nm. The output from the WSL is coupled into the multiplexed FBG array, which consists of five FBGs. The reflected Bragg wavelengths of the FBGs are 1,532.02 nm, 1,537.84 nm, 1,543.48 nm, 1,547.98 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…All these typologies of single- and multi-parameter OFS have interrogation based on spectral detection, which significantly differs from other approaches such as interferometry of intensity-based transducing [ 34 , 35 ]. Typical interrogation systems detect the spectrum reflected by the sensing structure on a wavelength interval ranging from 40 nm to 80 nm [ 36 , 37 , 38 , 39 ]. Most systems are based on a broadband light source and a spectrometer for detection [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…All these typologies of single- and multi-parameter OFS have interrogation based on spectral detection, which significantly differs from other approaches such as interferometry of intensity-based transducing [ 34 , 35 ]. Typical interrogation systems detect the spectrum reflected by the sensing structure on a wavelength interval ranging from 40 nm to 80 nm [ 36 , 37 , 38 , 39 ]. Most systems are based on a broadband light source and a spectrometer for detection [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The bandwidth of the WSL is greater than that of the ASE from the SOA. The dotted box in the figure represents the polygon-scanner-based wavelength filter, which consists of a polygon rotating mirror, a diffraction grating, and two achromatic doublet lenses [12].…”
Section: Nematic Liquid Crystal Fabry-perot Etalonmentioning
confidence: 99%
“…Another way is a swept source based on Fourier domain mode locking (FDML) technology, by introducing a several-kilometer single-mode fiber (SMF) in the cavity, meanwhile periodically driving the optical bandpass filter synchronously with the optical round-trip time of the light [8]. There are mainly four central wavelength swept sources, including 850 [9], 1050 [10][11][12], 1310 [4,8], and 1550 nm [13], used in the SSOCT system. It is demonstrated that SSOCT at the 1050 nm wavelength range is best for imaging in human retina and choroid layers, since the absorption of water at the 1050 nm range is lower than at the 1310 nm range, the scattering at the 1050 nm water window is reduced compared to that at 850 nm [10], and the dispersion of water near 1050 nm is zero [14].…”
Section: Introductionmentioning
confidence: 99%